Hepatoprotective and antioxidant effects of “Couroupita guianensis” on carbon tetra chloride - induced liver damage - Raja Sundararajan,; Ravindranadh Koduru, (International Journal of Phytomedicine, 2015)
To investigate the hepatoprotective and antioxidant activities of methanol leaves extract of Couroupita guianensis against carbon tetrachloride+ Olive oil -induced hepatotoxicity in rats. The hepatoprotective activity of methanol extract of leaves of Couroupita guianensis was evaluated against carbon tetrachloride + Olive oil -induced hepatic damage in rats. In-vivo antioxidant activity of methanol extract of leaves of Couroupita guianensis was evaluated by various assays including lipid peroxidation, super oxide dismutase, reduced glutathione, catalase, glutathione peroxidase, and glutathione reductase. The methanol extract of leaves of Couroupita guianensis at dose of 250 and 500 mg/kg were administered orally once daily for seven days. Serum enzymatic levels of serum glutamate oxaloacetate transaminase (SGOT), serum glutamate pyruvate transaminase (SGPT), serum alkaline phosphatase (SALP), bilirubin and Lactate dehyrogenase were estimated along with estimation of superoxide dismutase (SOD), reduced glutathione, catalase (CAT), glutathione peroxidase (GPx), glutathione reductase (GRD) and malondialdehyde (MDA) levels in liver tissues. Further histopathological examination of the liver sections was carried out to support the induction of hepatotoxicity and hepatoprotective efficacy. The substantially elevated serum enzymatic levels of SGOT, SGPT, ALP total bilirubin and total protein were found to be restored towards normalization significantly by the methanol extract of leaves of Couroupita guianensis in a dose dependent manner with maximum hepatoprotection at 500mg/kg dose level. The extract showed potent activities on reduced glutathione, SOD, CAT, GRD, GPx and MDA levels. The histopathological observations supported the biochemical evidences of hepatoprotection. The results of the present study strongly reveal that methanol extract of leaves of Couroupita guianensis has hepatoprotective and antioxidant activities against carbon tetrachloride -induced hepatic damage in experimental animals.